Effects of Vitamin D on Blood Pressure, Arterial Stiffness, and Cardiac Function in Older People After 1 Year: BEST‐D (Biochemical Efficacy and Safety Trial of Vitamin D). Issue 10 (24th October 2017) - Tomson, Joseph; Hin, Harold; Emberson, Jonathan; Kurien, Rijo; Lay, Michael; Cox, Jolyon; Hill, Michael; Arnold, Linda; Leeson, Paul; Armitage, Jane; Clarke, Robert
Abstract : Background: The relevance of vitamin D for prevention of cardiovascular disease is uncertain. The BEST‐D (Biochemical Efficacy and Safety Trial of vitamin D) trial previously reported effects of vitamin D on plasma markers of vitamin D status, and the present report describes the effects on blood pressure, heart rate, arterial stiffness, and cardiac function. Methods and Results: This was a randomized, double‐blind, placebo‐controlled trial of 305 older people living in United Kingdom, who were allocated vitamin D 4000 IU (100 μg), vitamin D 2000 IU (50 μg), or placebo daily. Primary outcomes were plasma concentrations of 25‐hydroxy‐vitamin D and secondary outcomes were blood pressure, heart rate, and arterial stiffness in all participants at 6 and 12 months, plasma N‐terminal prohormone of brain natriuretic peptide levels in all participants at 12 months, and echocardiographic measures of cardiac function in a randomly selected subset (n=177) at 12 months. Mean (SE) plasma 25‐hydroxy‐vitamin D concentrations were 50 (SE 2) nmol/L at baseline and increased to 137 (2.4), 102 (2.4), and 53 (2.4) nmol/L after 12 months in those allocated 4000 IU/d, 2000 IU/d of vitamin D, or placebo, respectively. Allocation to vitamin D had no significant effect on mean levels of blood pressure, heart rate, or arterial stiffness at either 6 or 12 months, nor on any echocardiographic measures of cardiac function, or plasma N‐terminal prohormone of brain natriuretic peptide concentration at 12 months. Conclusions: The absence of any significant effect of vitamin D on blood pressure, arterial stiffness, or cardiac function suggests that any beneficial effects of vitamin D on cardiovascular disease are unlikely to be mediated through these mechanisms. Clinical Trial Registration: URL:https://www.clinicaltrialsregister.eu/ctr-search/search . Unique identifier: EudraCT number: 2011–005763‐24a